Planos privados de saúde e cláusulas abusivas: uma análise dos princípios constitucionais violados nos casos de cláusulas que estabelecem período de carência - Fernandes, Alessandra Soares (2017)
It analyzes, through a brief historical context and the legal bias, the fundamental right to health, based on the Federal Constitution of 1988, demonstrating the new health policy after the Magna Carta, as well as the question of the "phenomenon" Health, since, normally, as a way of guaranteeing this right, the Judiciary appears as the protagonist. In addition, it highlights the constitutional and civil principles violated in cases of clauses that establish grace period. It should be noted that certain principles are violated, especially the Dignity of the Human Person and that of the Good Faith, and the Magistrate in this case must preserve the good of life, rather than the contractual good, thus stipulating indemnities. In this sense, the work fulfills the objective of considering the private health plans and abuses committed by these plans, especially the question about the grace period and constitutional principles violated, in view of the increasing demand for contracting these plans, But which in turn has increased the problems for consumers who need a particular plan, since the expansion of contracting health plans in the country has triggered a number of issues of a judicial nature, as seen in the course of the research. Lastly, it was stressed that there was a need for more effective supervision by the competent authorities, as well as the need for a restructuring of the existing Bodies and the practical establishment of the rules in force.